2018
DOI: 10.3171/2017.5.jns163266
|View full text |Cite
|
Sign up to set email alerts
|

Does the obesity paradox predict functional outcome in intracerebral hemorrhage?

Abstract: OBJECTIVE Being overweight or mildly obese has been associated with a decreased risk of death or hospitalization in patients with cardiovascular disease. Similarly, overweight patients admitted to an intensive care unit (ICU) have improved survival up to 1 year after admission. These counterintuitive observations are examples of the "obesity paradox." Does the obesity paradox exist in patients with intracerebral hemorrhage (ICH)? In this study the authors examined whether there was an association between obesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 18 publications
0
31
0
Order By: Relevance
“…8,28,33 Altogether, they have contributed to the weight gain in the population that lead to the fact that obesity is currently considered a pandemic. 8,28,34 Obesity is diagnosed as a BMI >30 kg/m 2 (calculated by the patient's weight in kilograms divided by the squared height in meters). 20,22,29,30,35,36 However, it is important to consider the world regions and countries, as the measurement can change somewhat.…”
Section: The Current Global Problem Of Stroke and Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…8,28,33 Altogether, they have contributed to the weight gain in the population that lead to the fact that obesity is currently considered a pandemic. 8,28,34 Obesity is diagnosed as a BMI >30 kg/m 2 (calculated by the patient's weight in kilograms divided by the squared height in meters). 20,22,29,30,35,36 However, it is important to consider the world regions and countries, as the measurement can change somewhat.…”
Section: The Current Global Problem Of Stroke and Obesitymentioning
confidence: 99%
“…As we previously mentioned, obesity predisposes an increased risk of suffering cardiovascular and systemic diseases, such as stroke and other diseases. 29,33,34,[47][48][49] It is associated with premature mortality; and, in multiple studies, a higher risk of cardiovascular disease incidence has been demonstrated in underweight adults or just overweight (but not obese) patients. As a result, there is no clear evidence of a higher prevalence or incidence of stroke in those with an obesity diagnosis.…”
Section: The Obesity Paradoxmentioning
confidence: 99%
“…According to this theory, overweight and obese people may have a survival benefit in various acute illnesses and medical conditions. In stroke subtypes other than SAH, such as intracerebral hemorrhage (ICH) [7,21] and ischemic stroke [20,22,35,45,47], being overweight or obese is associated with a favorable outcome. However, the true impact of BMI on the survival of any ICU patient group has remained unclear, and several studies have reported controversial results about the effects of obesity on the outcome of critically ill patients [1,16,31].…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Observation of obesity paradox in intracerebral hemorrhage is reported in fewer studies. Of interest for our study, Dangayach et al 37 reported an overweight or obese status (BMI 25 kg/m2) was associated with twice the odds of having a good outcome compared with patients with BMI less than 25 kg/m2. In the study by Kim et al 38 obesity was associated with a lower risk of longterm death but not with 30-day mortality after ICH.…”
Section: Discussionmentioning
confidence: 86%